KAWASAN BUDAYA BACA DI BANJARBARU - Irvanur Razaq Dwi Putra; Bani Noor Muchamad (ULM Press, 2021)
Reading Culture Area in Banjarbaru is a reading facility to increase the interest in literation and reading of the community in Banjarbaru. The architectural problem raised in this report is how to design a reading facility that is able to create a new innovation to attract public interest in reading by having interactive, educational and recreational values on it. The concept applied to the design of Reading Culture Area in Banjarbaru is a Hybrid Architecture method approach. Hybrid Architecture is a concept to unite space, form, technique and function using a method of combining two or more different things, so that a unique and new architecture will be created in a design.